2023
DOI: 10.3390/ijms24054844
|View full text |Cite
|
Sign up to set email alerts
|

Study on Anti-Constipation Effects of Hemerocallis citrina Baroni through a Novel Strategy of Network Pharmacology Screening

Abstract: Daylily (Hemerocallis citrina Baroni) is an edible plant widely distributed worldwide, especially in Asia. It has traditionally been considered a potential anti-constipation vegetable. This study aimed to investigate the anti-constipation effects of daylily from the perspective of gastro-intestinal transit, defecation parameters, short-chain organic acids, gut microbiome, transcriptomes and network pharmacology. The results show that dried daylily (DHC) intake accelerated the defecation frequency of mice, whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…LYD is widely distributed in Mongolia, Russia, China, Japan, Korea and Europe and is popular for its attractive flowers ( Guo et al 2022 , 2023 ). It is a material of choice in treating depression and has also shown antioxidant, anti-inflammatory, anti-constipation, anti-lactation deficiency and neuroprotective abilities ( Tian et al 2017 ; Matraszek-Gawron et al 2019 ; Zhong et al 2021 ; Ma et al 2022 , 2023 ; Jiang et al 2023 ; Liang et al 2023 ). It is a rich source of nutrients (amino acids, carbohydrates, phosphorus, calcium, iron, and vitamins C, B1, B2 and B5) and functional substances, such as lecithin, alkaloids, phenolic acids, flavonoids and saponins ( Guo et al 2022 ; Li et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…LYD is widely distributed in Mongolia, Russia, China, Japan, Korea and Europe and is popular for its attractive flowers ( Guo et al 2022 , 2023 ). It is a material of choice in treating depression and has also shown antioxidant, anti-inflammatory, anti-constipation, anti-lactation deficiency and neuroprotective abilities ( Tian et al 2017 ; Matraszek-Gawron et al 2019 ; Zhong et al 2021 ; Ma et al 2022 , 2023 ; Jiang et al 2023 ; Liang et al 2023 ). It is a rich source of nutrients (amino acids, carbohydrates, phosphorus, calcium, iron, and vitamins C, B1, B2 and B5) and functional substances, such as lecithin, alkaloids, phenolic acids, flavonoids and saponins ( Guo et al 2022 ; Li et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Liang et al [1] investigated the anti-constipation effects of Hemerocallis citrina Baroni (Daylily, DHC) on gastrointestinal transit, defecation parameters, short-chain organic acids, the gut microbiome, transcriptomes and network pharmacology. The authors demonstrated that the administration of DHC accelerates the defecation frequency of mice and elevates the abundance of some beneficial bacterial taxa while reducing the levels of pathogens in cecal contents.…”
mentioning
confidence: 99%